2002
DOI: 10.1152/ajplung.00358.2001
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal NAD+prevents diminished O2consumption by immunostimulated Caco-2 cells

Abstract: Accumulating data support the view that sepsis is associated with an acquired intrinsic derangement in the ability of cells to consume O 2, a phenomenon that has been termed "cytopathic hypoxia." We sought to use an in vitro "reductionist" model system using cultured cells stimulated with proinflammatory cytokines to test the hypothesis that cytopathic hypoxia is mediated, at least in part, by depletion of intracellular levels of NAD ϩ / NADH secondary to activation of the nuclear enzyme poly-(ADP-ribose) poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 43 publications
1
34
0
3
Order By: Relevance
“…An excessive stimulation of PARP-1 can lead to depletion of NAD + /NADH and can therefore interfere with the synthesis of ATP [76], leading to a state of cytopathic hypoxia and cell death. is has been studied in various cells, including macrophages and smooth muscle cells stimulated with oxidizing molecules [77], and enterocytes stimulated with proin ammatory cytokines and oxidizing molecules [78].…”
Section: Activation Of Enzymes In Ol Ed In Dna Damage Repair: Poly (Amentioning
confidence: 99%
“…An excessive stimulation of PARP-1 can lead to depletion of NAD + /NADH and can therefore interfere with the synthesis of ATP [76], leading to a state of cytopathic hypoxia and cell death. is has been studied in various cells, including macrophages and smooth muscle cells stimulated with oxidizing molecules [77], and enterocytes stimulated with proin ammatory cytokines and oxidizing molecules [78].…”
Section: Activation Of Enzymes In Ol Ed In Dna Damage Repair: Poly (Amentioning
confidence: 99%
“…There is also extensive evidence that T-cell signaling is affected by NAD ϩ , with ultimate effects on proliferation and apoptosis (22)(23)(24)(25)(26)(27)(28). Furthermore, several studies have shown that NAD ϩ can protect against inflammatory stress both in vitro and in vivo (29,30), in part via reduced activity of the central inflammatory transcription factor NF-B. 5 We have also found that treatment of endotoxemic mice with NAD ϩ could protect from lethality in the case of mice injected with high dose LPSs and greatly reduced plasma TNF-␣ and NO b Ϫ / NO 3 Ϫ and elevated IL-10 in mice subjected to low-dose LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of NAD ϩ , the precursor of cADPR, inhibits signaling via this pathway. Interestingly, we have reported that cytomix induces intracellular NAD ϩ depletion through an NO⅐-dependent process in Caco-2 cells (Khan et al, 2002). Whether cytomix-induced intracellular NAD ϩ depletion affects intracellular cADPR levels and [Ca 2ϩ ] i in Caco-2 cells remains to be investigated.…”
Section: Anti-inflammatory Activity Of Nadmentioning
confidence: 97%
“…During experiments designed to explore the biological effects of decreased intracellular NAD ϩ content in immunostimulated human Caco-2 enterocyte-like cells (Khan et al, 2002), we serendipitously observed that adding NAD ϩ to the culture medium ameliorated derangements in epithelial barrier function caused by exposing these cells to a mixture of proinflammatory cytokines, called "cytomix". This observation prompted us to review a growing literature regarding the role of NAD ϩ and closely related compounds as signaling molecules.…”
Section: Nadmentioning
confidence: 99%